Pena Tajam Patriot Muda: Peran Intelektual Burhanudin Mohamad Diah pada Masa Revolusi (1945-1949) - Muhammad Miqdad Rojab Munigar; Andi Suwirta; Wildan Insan Fauzi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This study is aims to explain Burhanudin Mohamad Diah (B.M. Diah) regarding his role, views, ideas, impact and responses toward his ideas during the Indonesia Revolusition in 1945 – 1949. This article is using historical method which consists of several steps, including: source search (heuristic), source criticism (internal and eksternal), interpretation and historigraphy. The result of this study indicating that during B.M. Diah’s journey as a journalist and politician, he gained a lot of experience while in school. During Indonesia revolution B.M. Diah has consistently expressed his four views and ideas through editorial header on Merdeka daily using alias Dr. Clenik. The four involved, the first is people unitarism that 100% independence within the framework of uniti is the will of the people. The second is the skepticism of the political manipulation carried bu the Ducth. Third, nationalism and identity crisis becoming phenomenom in Indonesia at the time. Fourth, there are also latent socialist in Indonesia B.M. Diah view’s, who was similar to the Partai Nasional Indonesia, had a fairly large impact on Komite Nasional Indonesia Pusat, and B.M. Diah had a bear various responeses as a consequence of his political activities and publications.